Using small numbers of subjects in fMRI-based research. - Savoy, R.L.
This article reviews a number of issues related to the special features and potentials associated with doing functional brain imaging experiments with one or a small number of subjects. It concludes with a speculation that, ironically, it may someday turn out that the information from a few brains, thoroughly studied, will reveal more about universal aspects of human brain function and organization than the current torrent of studies from large collections of brains.
Keywords: fMRI-based research; Functional brain imaging; Human brain; Small-subject fMRI